Assessing the Effectiveness of Geography-based Online Learning During the Covid-19 Pandemic in Higher Education - Abdul Wahab Abdi; Syahrul Ridha; Muhammad Yunus; Puspita Annaba Kamil; Intan Safiah; Ahmad Nubli Gadeng (Geosfera Indonesia, 2021)
The Covid-19 pandemic almost stalled the face-to-face learning method in all institutions across the globe. Consequently, for learning to continue uninterrupted, there was a need to change teaching mode to online using social media and other platforms. This research aimed to examine the effectiveness of online learning during the Covid-19 pandemic and the challenges geography students faced in implementing this type of study. The research used a descriptive qualitative approach involving questionnaires designed to determine the implementation of online learning and the challenges encountered. The questions were structured through synthesizing various components of learning. Random selection was used to select 305 participants from various higher education institutions in the Aceh Region, Indonesia. The results indicated that online learning during the Covid-19 pandemic was effectively implemented. However, some challenges were encountered, including students who could not fully participate since they could not log in to the provided learning platforms. Furthermore, students from rural areas had poor internet connectivity besides the inability to buy internet quota. There were many instances of reported power supply failures, and this hindered online learning. Overall, learning geography during the pandemic was effective, though it had a fair share of challenges. The research also identified the need to develop an online learning model, teaching material, and multimedia in supporting geography-based online learning. Keywords: Assessing; Effectiveness; Geography-based online learning; Covid-19; Higher education Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License